Examine The Role of Customer Hope in Explaining The Impact of Brand Charisma on Results of Relationship Between Online Purchase Intentions and Superior Customer Value: Users of Apple Smartphone Products As A Model - Saif Ali Jasim (Research Parks Publishers, 2026)
The purpose of the current research is to examine the role of customer hope in explaining the impact of brand attractiveness on the relationship between online purchase intentions represented in (perceived benefit, perceived ease of use, and trend towards use) and the superior customer value, and therefore the research aimed to examine the impact of the attractiveness of the mark on online purchase intentions and the superior customer value through the customer's hope, and accordingly customer opinions were surveyed towards Apple products as a model of (697) online shoppers, The results were interpreted based on SPSS&SMART.PLS) by extracting means, standard deviations, Cronbach’s alpha reliability coefficient, correlation coefficient, regression coefficient, interpretation coefficient, and critical value, The results showed that brand attractiveness has a positive impact on customer hope, and that customer hope is strongly correlated with online purchase intentions and superior customer value, but in theory this model highlights the statement of the role played by customer hope in the relationship between brand attractiveness and online purchase intentions and superior customer value.